Highly Active and Durable Nanostructured Nickel‐Molybdenum Coatings as Hydrogen Electrocatalysts via Solution Precursor Plasma Spraying - Xiuyu Wu; Alexis Piñeiro‐García; Mouna Rafei; Alice Kuzhikandathil; Esdras J. Canto‐Aguilar; Eduardo Gracia‐Espino (ChemistryOpen)
Abstract The increasing demand for green hydrogen is driving the development of efficient and durable electrocatalysts for the hydrogen evolution reaction (HER). Nickel‐molybdenum (NiMo) alloys are among the best HER electrocatalysts in alkaline electrolytes, and here we report a scalable solution precursor plasma spraying (SPPS) process to produce the highly active Ni4Mo electrocatalysts directly onto metallic substrates. The NiMo coating coated onto inexpensive Ni mesh revealed an excellent HER performance with an overpotential of only 26 mV at −10 mA cm−2 with a Tafel slope of 55 mV dec−1. Excellent operational stability with minimum changes in overpotential were also observed even after extensive 60 hour high‐current stability test. In addition, we investigate the influence of different substrates over the catalytic performance and operational stability. We also proposed that a slow, but consistent, dissolution of Mo is the primary degradation mechanism of NiMo‐based coatings. This unique SPPS approach enables the scalable production of exceptional NiMo electrocatalysts with remarkable activity and durability, positioning them as ideal cathode materials for practical applications in alkaline water electrolysers.